THE IMAGE OF THE PARENT FAMILY OF ADULTS WITH MENTAL DISABILITIES - Khazova, Svetlana; Adeeva, Tatiana; Maiorova, Maria; Tikhonova, Inna; Shipova, Natalya (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Тhe article is devoted to the study of the image of the parent family of adults with mental disabilities, as this problem is little studied in modern psychology. Sample: 39 people with mental disorders aged 18 to 47 years. Research method: clinical semi-structured interview and projective methods. The results indicate that the majority of adults with mental disorders were brought up in families: 44% - in a full family, 12% - only with the mother, 3% - in the families of grandparents. Many of them continue to live with their parents and now. Communication in the family is often evaluated positively, memories are associated with parents or other family members. The respondents of this group experienced the death of loved ones. 41% of adults with mental disorders were sent by parents to special boarding schools, while half of them never saw their parents and did not communicate with them, and 14% were familiar with their parents, but had a negative experience with them. They noted generally positive plots, but they extremely seldom were connected with a family. At the same time, negative memories are often associated with the family. Respondents of both groups distinguish not only the positive characteristics of parents, but also note the importance of joint activities. The obtained data can be successfully used as a basis for further study of the relationship of the image of the parent family with the subjective well - being of adults with intellectual disabilities, as well as the development of the main targets of the psychotherapeutic process.